Environmental campaign in the documentary film Ekspedisi 3 Sungai episode Juara Sampah Saset - Hanief, Lalita; Ainani, Muhammad; Nurfatmawati, Atik (ProTVF, 2026)
Background: This research analyzes the function of environmental communication in the documentary film "Ekspedisi 3 Sungai Episode Juara Sampah Saset" which highlights the crisis of plastic waste pollution in the Brantas River. Purpose: Using a social constructivism paradigm and a qualitative-interpretative approach, this research examines how documentary films construct and communicate environmental messages to their audiences. Methods: Data were collected through documentary analysis of the films and interviews with environmental communication academics, documentary film practitioners, and environmental activists. Data analysis used qualitative content analysis method with Cox's environmental communication function framework. Results: An effective visual strategy, namely the depiction of the contrast between community activities and river conditions and the use of analogies in the narrative diction, has succeeded in creating an emotional atmosphere for the audience. The film is also successful in bridging the gap between issues of global concern on polluting the environment with the real life of the locals. The results of the waste audit that showed significant generation of single-use products waste in big companies give a fresh insight into the CSR program on the plastic waste crisis.  Conclusion: The documentary film Ekspedisi 3 Sungai Episode Juara Sampah Saset demonstrates that visual media can be a productive method of bringing complex environmental topics into the mass consciousness, incorporating both technical information and compelling stories to make people think about them. By using effective visual imagery and a brand audit style, the movie underlines corporate accountability toward plastic pollution, and relates macro problems to the micro-level experiences of the communities involved in supporting a moral thinking of waste disposal practices. Implications: The study will help in development of effective environmental communication strategies in Indonesia. Recommendations on how the more tangible effect of documentary movies on behavioral and waste management policy changes within a community can be quantified.